Implementasi Model Pembelajaran Project-Based Learning (PjBL) untuk Meningkatkan Pemahaman Akidah Akhlak pada Siswa Kelas V di SDN 77/I Penerokan, Bajubang, Batang Hari - Jamal, Ahmad; Putra, Hazanil; Nuraini, Nuraini (Asian Journal of Early Childhood and Elementary Education, 2025)
This study aims to analyze the effectiveness of implementing the Project-Based Learning (PJBL) model in enhancing students’ understanding of the Akidah Akhlak subject at SDN 77/I Penerokan, Bajubang District, Batang Hari Regency. The PJBL method was applied over one month in November 2024, involving students in real-world application-based projects, such as creating posters on ethical values, group discussions, and presentations. The results show that the PJBL method significantly improved students’ learning outcomes, with the average score rising from 65 to 80. The percentage of students meeting the Minimum Mastery Criterion (KKM) of 75 increased from 28% to 84%, while the percentage of students not meeting the KKM decreased from 72% to 16%. Additionally, student participation in the learning process increased from 35% to 85%, demonstrating that PJBL effectively boosted student motivation and active engagement. PJBL also positively impacted the development of 21st-century skills, such as critical thinking, collaboration, and effective communication. These findings support Thomas (2000), who stated that PJBL enhances student engagement through practical and applicable learning approaches, and Hmelo-Silver (2004) in (Indah et al., 2024), who confirmed that PJBL effectively improves students’ abilities to solve complex problems and work collaboratively in groups. However, the study noted several challenges, including difficulties in task distribution during the initial implementation phase and time management issues. These obstacles were addressed through additional teacher guidance, schedule adjustments, and more structured task allocation. Overall, the results of this study indicate that PJBL is an innovative and effective teaching method for improving students’ understanding of Akidah Akhlak material while simultaneously developing non-academic skills. With its real-world project-based approach, PJBL creates more practical, meaningful learning experiences and motivates students to engage in active learning. The study recommends implementing PJBL in other subjects at the elementary level to improve overall teaching quality. Additionally, intensive training and continuous evaluation are needed to enable teachers to design and execute PJBL optimally. With further development, PJBL can serve as a solution to enhance the quality of education at the elementary level, particularly in value-based learning such as Akidah Akhlak.